EFL student teachers’ learning in a peer-tutoring research study group - Viáfara, John Jairo (Colombian Applied Linguistics Journal, 2014)
In order to become peer-tutors in a BA program in Modern Languages, a group of English as a Foreign Language (EFL) student teachers attended a study and research group in a university. Throughout their participation, prospective teachers collaborated and reflected by means of task completion and dialogue to learn the theory and practice of tutoring and research. Additionally, participants provided survey, journal, and interview data to contribute to the exploration of how their group membership shaped them academically and personally. Results suggested that student teachers increased their knowledge of English due to their use of real-life group dynamics, among others. Furthermore, they updated and expanded their competencies to monitor pedagogical situations, design strategies, and solve problems.